Actin Modulation Regulates the Alpha-1-Syntrophin/p66Shc Mediated Redox Signaling Contributing to the RhoA GTPase Protein Activation in Breast Cancer Cells - Ali, Roshia; Mir, Hilal Ahmad; Hamid, Rabia; Bhat, Basharat; Shah, Riaz A.; Khanday, Firdous A.; Bhat, Sahar Saleem (Frontiers in Oncology, 2022)
SNTA1 signaling axis plays an essential role in cytoskeletal organization and is also implicated in breast cancers. In this study, we aimed to investigate the involvement of actin cytoskeleton in the propagation of SNTA1/p66shc mediated pro-metastatic cascade in breast cancer cells.The effect of actin filament depolymerization on SNTA1-p66Shc interaction and the trimeric complex formation was analyzed using co-immunoprecipitation assays. Immunofluorescence and RhoA activation assays were used to show the involvement of SNTA1-p66Shc interaction in RhoA activation and F-actin organization. Cellular proliferation and ROS levels were assessed using MTT assay and Amplex red catalase assay. The migratory potential was evaluated using transwell migration assay and wound healing assay.We found that cytochalasin D mediated actin depolymerization significantly declines endogenous interaction between SNTA1 and p66Shc protein in MDA-MB-231 cells. Results indicate that SNTA1 and p66Shc interact with RhoA protein under physiological conditions. The ROS generation and RhoA activation were substantially enhanced in cells overexpressing SNTA1 and p66Shc, promoting proliferation and migration in these cells. In addition, we found that loss of SNTA1-p66Shc interaction impaired actin organization, proliferation, and migration in breast cancer cells. Our results demonstrate a novel reciprocal regulatory mechanism between actin modulation and SNTA1/p66Shc/RhoA signaling cascade in human metastatic breast cancer cells.